PENYELIDIKAN GEOLISTRIK MENGGUNAKAN KONFIGURASI SCHLUMBERGER TERHADAP POTENSI AMBLESAN DAERAH PONJONG, GUNUNG KIDUL - Rizqi, Al Hussein Flowers; Yudhana, Waskita Murti Bambang (Institut Teknologi Nasional Yogyakarta, 2020)
Administratively, the research area is included in Ponjong Subdistrict, Gunung Kidul Regency, Special Region of Yogyakarta. Geographically, it’s located in 07°56’30